(untitled) (Journal of the College of Basic Education, 2022)
The objective of the current research is to identify (the effect of using the Van Hiele model on the achievement of fifth-grade students in scientific concepts in science), by verifying the following null hypothesis:1- There is no statistically significant difference at the level of significance (0.05) between the average achievement scores of the students of the experimental group taught according to the Van Hiele model and the average scores of the students of the control group taught according to the usual method in the achievement test for scientific concepts.The experimental design with partial control was chosen for the two groups (experimental and control) that control each other